2016
DOI: 10.1016/j.sleep.2016.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Sleep characteristics in type 1 diabetes and associations with glycemic control: systematic review and meta-analysis

Abstract: T1D was associated with poorer sleep and high prevalence of OSA. Poor sleep quality, shorter sleep duration, and OSA were associated with suboptimal glycemic control in T1D patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
176
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(203 citation statements)
references
References 59 publications
(139 reference statements)
21
176
2
4
Order By: Relevance
“…Our findings of a positive association between poor sleep quality and glycemic control in univariate analysis are similar previous reports . A prospective study enrolling patients with T1D reported that sleeping difficulties at baseline were significantly associated with higher HbA1c values at the 1‐year follow‐up .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings of a positive association between poor sleep quality and glycemic control in univariate analysis are similar previous reports . A prospective study enrolling patients with T1D reported that sleeping difficulties at baseline were significantly associated with higher HbA1c values at the 1‐year follow‐up .…”
Section: Discussionsupporting
confidence: 90%
“…The effect of sleep behavior (short or long sleep duration, sleep timing and quality) on health outcomes in patients with both T1D and type 2 diabetes (T2D), has received increasing attention. Referring only to T1D, clinical studies have shown that short sleep duration, poor sleep quality, and a low percentage of non‐rapid eye movement (REM) sleep, indicating shallow sleep, were associated with higher HbA1c levels . The prevalence of sleep disturbances is higher in patients with T1D than in the general population: a recent meta‐analysis that included 22 clinical studies showed that the prevalence of sleep disturbances is high among patients with T1D, who also have a lower quality of sleep compared with controls .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in line with findings from a recent study of adults with T1D, (20) but the current study is the first, to our knowledge, to demonstrate these relationships in the adolescent population. In addition, the lack of a significant association between sleep duration and glycemic control may explain why sleep has not been consistently associated with glycemic control in other studies of children and adolescents with T1D (10). Our findings suggest that, although obtaining sufficient sleep is important for good overall health, it may be even more valuable to consider consistency and timing of sleep in adolescents with T1D (31).…”
Section: Discussionmentioning
confidence: 95%
“…Of these, the predominant focus has centered on describing the associations between sleep duration and quality with glycemic control. For example, in a meta-analysis of 22 studies of sleep in people of all ages with T1D, Reutrakul and colleagues found that children and adolescents with T1D obtained significantly less sleep than youth without diabetes, with a mean difference of 26 minutes, but found no significant association between sleep duration and glycemic control in children and adolescents [7]. These findings must be interpreted with caution, however, given that only 3 small studies of children and adolescents were included (n=70 with T1D).…”
Section: Introductionmentioning
confidence: 99%